A qualitative transcriptional signature of recurrence risk for stages II–III gastric cancer patients after surgical resection. Issue 9 (18th February 2021) - Zhang, Huarong; Li, Xiangyu; Wu, Junling; Zhang, Jiahui; Huang, Haiyan; Li, Yawei; Li, Meifeng; Wang, Shanshan; Xia, Jie; Qi, Lishuang; Chen, Ting; Ao, Lu
Abstract: Background and Aim: Metastasis is the leading cause of recurrence in gastric cancer. However, the imaging techniques and pathological examinations for tumor metastasis have a high false‐positive rate or a high false‐negative rate, and many proposed that metastasis‐related molecular biomarkers can hardly be validated in independent datasets. Methods: We propose to use significantly stable gene pairs with reversal relative expression orderings (REOs) between non‐metastasis and metastasis gastric cancer samples as the metastasis‐related gene pairs. Based on the REOs of these gene pairs, we developed a qualitative transcriptional signature for predicting the recurrence risk of stages II–III gastric cancer patients after surgical resection. Results: A REOs‐based signature, consisting of 19 gene pairs (19‐GPS), was selected from 77 stages II–III gastric cancer patients and validated in two independent datasets. Samples in the high‐risk group had shorter disease‐free survival time and overall survival time than those in the low‐risk group. Differentially expressed genes (DEGs) between the high‐ and low‐risk groups classified by 19‐GPS were highly reproducible comparing with those between lymph node metastasis and lymph node non‐metastasis groups. Functional enrichment analysis showed that these DEGs were significantly enriched in metastasis‐related pathways, such as PI3K‐Akt and Rap1 signaling pathways. The multi‐omics analyses suggested that the epigenetic and genomic features might cause transcriptional differences between two subgroups, which help to characterize the mechanism of gastric cancer metastasis. Conclusions: The signature could robustly identify patients at high recurrence risk after resection surgery, and the multi‐omics analyses might aid in revealing the metastasis‐related characteristics of gastric cancer.